2022
DOI: 10.1021/acsapm.2c00614
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and Extendable Boronate-Based Tunable Hydrogel Networks for Patterning Applications

Abstract: Hydrogel patterning is an emerging area of interest and a valuable tool for studying cellular interactions. However, patterning of hydrogels is normally performed with photo-cross-linkable moieties, severely limiting the choice of materials that can be used. Dynamic covalent cross-linked systems show highly desirable properties as they can show covalent and noncovalent characteristics in response to different environmental conditions, therefore allowing for a potential switch in hydrogel properties. To expand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…However, their fast relaxation and lack of stability in culture medium usually do not allow them to maintain a predefined shape for extended periods of time. To take advantage of their extrudability, BE hydrogels have been combined with additional cross-linking strategies that allow for postprinting stabilization . For example, a study reported the association of alginate, which contains diol groups, with PBA-modified laminarin (a polymer extracted from brown algae) to produce a BE hydrogel that can be stabilized by ionic cross-linking with calcium ions .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their fast relaxation and lack of stability in culture medium usually do not allow them to maintain a predefined shape for extended periods of time. To take advantage of their extrudability, BE hydrogels have been combined with additional cross-linking strategies that allow for postprinting stabilization . For example, a study reported the association of alginate, which contains diol groups, with PBA-modified laminarin (a polymer extracted from brown algae) to produce a BE hydrogel that can be stabilized by ionic cross-linking with calcium ions .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…To take advantage of their extrudability, BE hydrogels have been combined with additional cross-linking strategies that allow for postprinting stabilization. 188 For example, a study reported the association of alginate, which contains diol groups, with PBA-modified laminarin (a polymer extracted from brown algae) to produce a BE hydrogel that can be stabilized by ionic cross-linking with calcium ions. 189 For 3D printing, each printed hydrogel layer was sprayed with CaCl 2 allowing the authors to print an 8-layer construct (3.2 mm height, 10 mm diameter) without structural collapse.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…This tunable and flexible system has the potential to be a handy tool for biological applications such as studying the cellular response to environmental changes and 3D printing applications. 125 Besides, Hsu and coworkers developed a 3D-printable and glucose-sensitive boronate ester hydrogel for the construction of constructs with vascular-like channels using a commercial 3D bioprinter. 126 In this system, the combination of a sacrificial boronate ester hydrogel and a non-sacrificial gel was required to fabricate a vascularized pattern in the construct.…”
Section: Applications Of Functional Polymers Based On Dynamic B–o Bondsmentioning
confidence: 99%
“…15b). 125 The pre-gels were extendable and could be pulled into thin strands, which subsequently could be patterned into thin lines. The pre-gels were also capable to be integrated into hydrogel printing to create standing 3D structures.…”
Section: Other Emerging Applicationsmentioning
confidence: 99%
“…The reversibility of these bonds have resulted in the formation of hydrogel with good self‐healing property [5] . Furthermore, these boronate‐based systems can be pulled into thin strings and used for hydrogel printing [4e] . These dynamic covalent bonds have also been introduced due to their high stability, as well as reprocessability under specific conditions [6]…”
Section: Introductionmentioning
confidence: 99%